Leadership Cadre in Madrasah: Strategies for Finding The Ideal Leader in Islamic Educational Institutions - Subiyantoro, Subiyantoro (Nurul Jadid University, Probolinggo, East Java, Indonesia, 2022)
This study aims to understand leadership regeneration at Madrasah Aliyah Asy-Syafi'iyah Kendari to produce ideal leaders for the advancement of the institution. This study uses a qualitative approach to phenomenology, where the researcher tries to understand the meaning behind the phenomena that occur in the field. The data collection technique is done through in-depth interviews, observation, and documentation. The data analysis was carried out in stages, including data collection, data reduction, data presentation, and conclusions. The study results indicate that regeneration in leadership in madrasas is essential to create ideal leaders and good governance. The role of regeneration, including the inheritance of good organizational values, guarantor of organizational sustainability, and learning facilities for new cadres and prospective leaders of Islamic educational institutions. The cadre refers to standardization and formalization of the division of labor and specialization, the hierarchy of authority, professionalization, and written documentation.